1984
DOI: 10.1128/mcb.4.7.1206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a proto-oncogene (proto-myb) in hemopoietic tissues of mice.

Abstract: This study addressed the possibility that proto-myb (also called c-myb), the cellular homolog of a retroviral transforming gene, plays a role in hemopoiesis, particularly during maturation of T cells. By gel blot hybridization, we confirmed previous reports that proto-myb transcripts are found at much higher levels in thymic lymphocytes and cells of the erythroid lineage than in other tissue sources. Using dot blot hybridizations, we demonstrated further that similar levels of proto-myb expression are found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 37 publications
4
79
1
Order By: Relevance
“…However, mature myeloid cells and megakaryocytes appeared to completely lack c-myb expression at at day 16.5. Consistent with previous Northern blot analyses of c-myb expression (Sheiness and Gardinier, 1984;Thompson et al, 1986), strong c-myb signal is found in the bone marrow, but it is con®ned to blastoid cells. These bone marrow cells are likely precursors of erythroid and myeloid lineages (Figure 1e and f) and cells with terminally di erentiated myeloid features of multilobed nuclei had undetectable c-myb expression.…”
supporting
confidence: 90%
“…However, mature myeloid cells and megakaryocytes appeared to completely lack c-myb expression at at day 16.5. Consistent with previous Northern blot analyses of c-myb expression (Sheiness and Gardinier, 1984;Thompson et al, 1986), strong c-myb signal is found in the bone marrow, but it is con®ned to blastoid cells. These bone marrow cells are likely precursors of erythroid and myeloid lineages (Figure 1e and f) and cells with terminally di erentiated myeloid features of multilobed nuclei had undetectable c-myb expression.…”
supporting
confidence: 90%
“…Among the Myb family proteins (A-myb, B-myb, c-myb), c-myb expression has been considered to be an indicator of hematopoietic cell proliferation since the level of expression is high in the thymus and in the bone marrow, and its downregulation occurs as an early event in cellular differentiation (Oh and Reddy, 1999). In thymus, c-myb is selectively expressed in the cortex, and the expression is much lower in the medulla which behaves like immune competent peripheral T cells (Sheiness and Gardinier, 1984). Taken together, Dmp1 and c-myb may play complementary roles in early (c-myb) and late (Dmp1) thymic T-lymphocyte development and proliferation.…”
Section: Specific Expression Of Dmp1 In Nonproliferating Cellsmentioning
confidence: 99%
“…1 c-MYB is expressed at high levels in immature hematopoietic cells, 2 and the c-Myb protein plays an important role in growth regulation and differentiation in these cells. [3][4][5] Targeted disruption of the c-MYB locus in mice resulted in neonatal death due to failure of effective fetal hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%